2020
DOI: 10.1021/acs.jafc.0c03971
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Cassia Oil Emulsions Stabilized by Chitin Nanofibrils: Physicochemical Properties and Antibacterial Activities

Abstract: Nowadays consumers are increasingly demanding food with fewer synthetic preservatives, which makes antimicrobial essential oils (EOs) from plants promising alternatives. In this work, surfactant-free emulsions were successfully fabricated from Cinnamon cassia oil (C. cassia oil) with partially deacetylated chitin nanofiber (ChNF) adopted as a Pickering stabilizer. The storage stability and microstructures of the emulsions with different concentrations of ChNF were studied in detail. As ChNF concentration incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 53 publications
(131 reference statements)
1
20
0
Order By: Relevance
“…This result highlights the importance of the screening stage of the emulsion process parameters since the most stable emulsions presented similar characteristics of drop size, physical-chemical properties, and antimicrobial properties, even with different solid-phase concentrations. Huang et al prepared Cinnamon Cassia emulsions stabilized by chitin nanofibrils and reported a strong influence of solid content on antimicrobial properties [57]. These findings corroborate the discussion made above regarding the nanocellulose morphologies and their interaction with the EOs.…”
Section: Antimicrobial Testssupporting
confidence: 74%
“…This result highlights the importance of the screening stage of the emulsion process parameters since the most stable emulsions presented similar characteristics of drop size, physical-chemical properties, and antimicrobial properties, even with different solid-phase concentrations. Huang et al prepared Cinnamon Cassia emulsions stabilized by chitin nanofibrils and reported a strong influence of solid content on antimicrobial properties [57]. These findings corroborate the discussion made above regarding the nanocellulose morphologies and their interaction with the EOs.…”
Section: Antimicrobial Testssupporting
confidence: 74%
“…The zeta potential of dispersed-phase droplets can affect the stability of the emulsion interface, especially in different application environments (whether or not effectively protect and enhance the absorption of substances in simulated gastrointestinal environments), thus indirectly affecting the load capacity and availability of delivery active ingredient. In particular, when the antibacterial emulsion loaded with antibacterial active substances plays a role, the zeta potential of dispersed phase droplets will directly affect the contact with Gram-positive bacteria and Gram-negative bacteria, thereby affecting the antibacterial performance of the loaded antibacterial substances [ 25 , 33 ].…”
Section: Applications On the Dispersed-phase Scalementioning
confidence: 99%
“…(3) The structuring agent mainly refers to the material unable to adsorb onto interface but rather relies on matrix formation, which enhance the 3D reticular structure in the bulk, which are advantageous to bridge, connect, and immobilization the different droplets more compactly. According to their action mechanism, the emulsifying stabilizers can be divided into traditional emulsifiers (mainly relying on good amphiphilic properties) (such as surfactant, mixed emulsifier, conjugated emulsifier, and multi-layer emulsifier) ( Figure 4 A–D) [ 17 , 20 , 21 , 24 ]; Pickering-type emulsifiers (mainly relying on the partial wettability of particles and relatively structural integrity to achieve the irreversible interface adsorption) (such as micro/nanoparticles, which can exist in various forms, e.g., fibers, spherical, microgels, nanogels fibrils, and hollow nanoparticles) ( Figure 4 E–I) [ 13 , 33 , 35 , 39 , 43 , 44 , 53 ]; and structural agents ( Figure 4 J). Moreover, irrespective of their type, emulsifying stabilizers should exhibit appropriate particle sizes, morphological characteristics, and amphiphilicity to ensure that they stabilize the internal phase and help to preserve its structural stability in the continuous phase [ 4 ].…”
Section: Applications On the Interface Structure Scalementioning
confidence: 99%
“…Moreover, the effectiveness of NCh in stabilizing the oil/water interfaces has been demonstrated given its interfacial wettability, 44 leading to high droplet surface coverage. 45,46 While NCh is a good Pickering stabilizer on its own, [47][48][49][50] there is the possibility to tailor its interfacial adsorption if it is combined with other components, such as CNF. [51][52][53] In fact, here we propose such systems to achieve enhanced stability, for example, to variations in pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…An option is the naturally derived chitin, a cationic, insoluble polysaccharide bearing surface acetyl amine groups. , Among colloidal nanoparticles derived from chitin, fibril-like nanochitin (NCh) can be easily produced by mechanical disintegration under acidic conditions. Moreover, the effectiveness of NCh in stabilizing the oil/water interfaces has been demonstrated given its interfacial wettability, leading to high droplet surface coverage. , While NCh is a good Pickering stabilizer on its own, there is the possibility to tailor its interfacial adsorption if it is combined with other components, such as CNF. In fact, here, we propose such systems to achieve enhanced stability, for example, to variations in pH and ionic strength.…”
Section: Introductionmentioning
confidence: 99%